The contribution of Aníbal Quijano’s thought during his time at FLACSO and ECLAC in Chile (1959-1971) - Peña Aymara, Shyrley Tatiana (2026)
This article aims to analyze the life and main contributions of Aníbal Quijano Obregón (1930-2028), a renowned Peruvian sociologist, during his stay in Chile at the Faculty of Social Sciences (1959-1962) and his time as Director of the Social Affairs Division of the Economic Commission for Latin America and the Caribbean (1966-1971). Based on an exhaustive review of the literature, this article presents his interesting biography, which has been little studied by Latin American intellectuals, in order to understand how, specifically, his experience at FLACSO-Chile, his return to Peru as a university professor, and his time at ECLAC shaped his thinking in the social sciences. What works were produced during those years and what were the main topics addressed? These questions seek to contribute to Quijano’s vast legacy for reinterpretations and reevaluations of his thinking.